Local structure of indium oxynitride from x-ray absorption spectroscopy - J. T. Thienprasert (2018)
Synchrotron x-ray absorption near edge structures (XANES) measurements of In L3 edge is used in conjunction with first principles calculations to characterize rf magnetron sputtered indium oxynitride at different O contents. Good agreement between the measured and the independently calculated spectra are obtained. Calculations show that the XANES spectra of this alloy are sensitive to the coordination numbers of the In atoms, i.e., fourfold for indium nitride-like structures and sixfold for indium oxide-like structures, but not to the substitution of nearest neighbor N by O or vice versa. © 2008 American Institute of Physics.